1985
DOI: 10.1007/bf00698300
|View full text |Cite
|
Sign up to set email alerts
|

Luyso-pallido-nigral atrophy and amyotrophic lateral sclerosis

Abstract: The clinical and pathologic findings in a 34-year-old woman with basal ganglia degeneration and amyotrophic lateral sclerosis are reported. The duration of symptoms was 2 years. A maternal uncle had a parkinsonian syndrome with onset at 45 years of age. Neuropathologic examination revealed extensive neuronal loss and gliosis in the corpus Luysii. Nerve cell loss and gliosis also involved both parts of the globus pallidus, and the substantia nigra. The corticospinal tracts were demyelinated in the spinal cord, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 8 publications
3
33
1
Order By: Relevance
“…Nevertheless, in the occasional patient an isolated involvement of pallidum and pyramidal system matching a PPD might be found. Our study, however, suggests that these particular patients probably do not suffer from Davison's idiopathic PPD/S but that further investigations or follow‐up will ultimately deliver the correct diagnosis similar to the reported cases in which Davison's PPD/S was initially considered, but eventually excluded after further investigaton 57, 58, 63, 67, 68. Further studies in patients with Kufor‐Rakeb disease and FBXO7 mutations have to provide an answer to the question whether pallidopyramidal degeneration does exist in these cases.…”
Section: Resultssupporting
confidence: 61%
“…Nevertheless, in the occasional patient an isolated involvement of pallidum and pyramidal system matching a PPD might be found. Our study, however, suggests that these particular patients probably do not suffer from Davison's idiopathic PPD/S but that further investigations or follow‐up will ultimately deliver the correct diagnosis similar to the reported cases in which Davison's PPD/S was initially considered, but eventually excluded after further investigaton 57, 58, 63, 67, 68. Further studies in patients with Kufor‐Rakeb disease and FBXO7 mutations have to provide an answer to the question whether pallidopyramidal degeneration does exist in these cases.…”
Section: Resultssupporting
confidence: 61%
“…Our case had no familial history, and gait disturbance was the initial symptom, observed at the age of 68, and died after a 3‐year evolution of the disease. In the eight cases, family histories were reported in the two early‐onset cases (onset at the age of 29 and 32) . A patient reported by Kato et al developed the disease at the age of 20 with an unusually long, 31‐year disease duration .…”
Section: Discussioncontrasting
confidence: 58%
“…Degeneration can spread widely in ALS cases after long‐term survival with artificial respiratory support. Motor neuron diseases with PNLD are rare, and the number of reported cases is limited . Although the precise frequency remains unclear, Piao et al reported that PNL degeneration was observed in two cases among the 102 autopsied ALS cases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the PNLA described here represents simple multisystem degeneration manifested by neuronal loss and gliosis, without tau, α–synuclein, or polyglutamine accumulation. Association of PNLA with ALS (or MND) has been described in several cases 21–26 . We found two examples in a series of 102 autopsy‐confirmed cases of sporadic ALS, in which spinal anterior horn ubiquitin‐positive inclusions were present, but no dementia, extrapyramidal symptoms, or cortical ubiquitin‐positive inclusions 27 .…”
Section: Discussionmentioning
confidence: 76%